Money-- master the game 7 simple steps to financial freedom - Robbins, Anthony; Bobb, Jeremy (New York : Simon & Schuster Audio, 2014)
Based on extensive research and one-on-one interviews with more than 50 of the most legendary financial experts in the world-- from Carl Icahn and Warren Buffett to Ray Dalio and Steve Forbes-- Tony Robbins has created a simple 7-step blueprint that anyone can use for financial freedom as well as a lifetime income plan.
Unabridged.
Compact discs.
Includes pdf of worksheets and planning tools on disc 1.
Read by Jeremy Bobb and Tony Robbins.
Keywords: Finance, Personal; Investments; Audiobooks